Formulasi Sabun Susu Antibakteri Dari Daun Kelor (Moringa Oleifera Lam) dan Minyak Cengkih - Lutfia Jamlika Laduni; Anindya Utami Siamsasi; Jothy Andini (Al-Hayat: Natural Sciences, Health & Environment Journal, 2025)
Skin is the outermost part of the human body which functions to protect the inner body from external disturbances such as protecting the body from attacks by bacteria, fungi, disease germs and sunlight. Therefore, skin cleanser is needed as protection, namely bath soap. Bath soap can be divided into two types, namely solid soap and liquid soap. Solid soap is soap made using Potassium Hydroxide (KOH) while liquid soap is made by reacting Sodium Hydroxide (NaOH). Add fillers in the form of Moringa leaf extract and clove oil to the soap making process as antibacterial ingredients. The flavonoid and antibacterial content in Moringa leaf extract can repel free radicals. The aim of this research was to determine the effect of Moringa leaf extract and clove oil on soap quality. The soap making method uses a cold process. Moringa leaf extract. Based on the soap test results, the highest water content was obtained, namely 4.64%, the pH value was between 9-9.5, and the antibacterial test results with the largest inhibitory power were 2.2 cm.